Skp, Cullin, F-box (SCF)-Met30 and SCF-Cdc4-Mediated Proteolysis of CENP-A Prevents Mislocalization of CENP-A for Chromosomal Stability in Budding Yeast - Au, Wei-Chun (2020)
Restricting the localization of the histone H3 variant CENP-A (Cse4 in yeast, CID in flies) tocentromeres is essential for faithful chromosome segregation. Mislocalization of CENP-Aleads to chromosomal instability (CIN) in yeast, fly and human cells. Overexpression andmislocalization of CENP-A has been observed in many cancers and this correlates withincreased invasiveness and poor prognosis. Yet genes that regulate CENP-A levels andlocalization under physiological conditions have not been defined. In this study we used agenome-wide genetic screen to identify essential genes required for Cse4 homeostasis toprevent its mislocalization for chromosomal stability. We show that two Skp, Cullin, Fbox(SCF) ubiquitin ligases with the evolutionarily conserved F-box proteins Met30 andCdc4 interact and cooperatively regulate proteolysis of endogenous Cse4 and prevent itsmislocalization for faithful chromosome segregation under physiological conditions. Theinteraction of Met30 with Cdc4 is independent of the D domain, which is essential for theirhomodimerization and ubiquitination of other substrates. The requirement for both Cdc4and Met30 for ubiquitination is specifc for Cse4; and a common substrate for Cdc4 andMet30 has not previously been described. Met30 is necessary for the interaction betweenCdc4 and Cse4, and defects in this interaction lead to stabilization and mislocalization ofCse4, which in turn contributes to CIN. We provide the first direct link between Cse4 mislocalizationto defects in kinetochore structure and show that SCF-mediated proteolysis ofPLOS Genetics Cse4 is a major mechanism that prevents stable maintenance of Cse4 at non-centromericregions, thus ensuring faithful chromosome segregation. In summary, we have identifiedessential pathways that regulate cellular levels of endogenous Cse4 and shown that proteolysisof Cse4 by SCF-Met30/Cdc4 prevents mislocalization and CIN in unperturbed cells.